What do we know about extracellular vesicles in patients with idiopathic pulmonary fibrosis? a scoping review - Conti, Maria; Casara, Alvise; Turato, Graziella; Baraldo, Simonetta; Tinè, Mariaenrica; Semenzato, Umberto; Cocconcelli, Elisabetta; Biondini, Davide; Damin, Marco; Saetta, Marina; Cosio, Manuel G.; Balestro, Elisabetta; et al. (Frontiers in Immunology, 2025)
Extracellular Vesicles (EVs), released by all cell types and detectable in biological samples, carry a variety of biological molecules. These molecules mediate communication and signaling with both local and distant cells, potentially playing a role in the pathogenesis of diseases, including Interstitial Lung Diseases and, more specifically, Idiopathic Pulmonary Fibrosis. To better understand the role of EVs in IPF, a systematic search was performed in PubMed, Scopus, and Ovid databases. These searches were conducted from January 1st, 2019, the period during which the MISEV 2018 guidelines were published, to August 31st, 2024. The SANRA scale was used for quality assessment. A total of 691 papers were screened, and 16, in the end, were definitively enrolled for our evaluation. The studies were reviewed in the following steps: 1) the nomenclature used to define EVs; 2) conformity with the MISEV 2018 guidelines; 3) the biological samples used to isolate EVs; 4) the main conclusion of each manuscript. There was significant heterogeneity among the publications in all the aforementioned steps, such as the type and source of EVs and the analysis of EVs content, primarily a wide array of different miRNAs in the various publications. Despite these differences, the emerging role of EVs and their potential usefulness both in therapies and clinical practice is of growing interest.